2016
DOI: 10.1016/j.watres.2016.04.035
|View full text |Cite
|
Sign up to set email alerts
|

High salinity in molasses wastewaters shifts anaerobic digestion to carboxylate production

Abstract: Biorefinery wastewaters are often treated by means of anaerobic digestion to produce biogas. Alternatively, these wastewaters can be fermented, leading to the formation of carboxylates. Here, we investigated how lab-scale upflow anaerobic sludge blanket reactors could be shifted to fermentation by changing organic loading rate, hydraulic retention time, pH, and salinity. A strong increase in volatile fatty acid concentration up to 40 g COD L(-1) was achieved through increasing salinity above 30 mS cm(-1), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…However, methane production was reduced from 200 to less than 70 L CH 4 kg −1 VS in period c, indicating potential disturbance of the anaerobic process, while the acetate content was more than 35 mmol L −1 . This observation is in line with the results of De Vrieze et al who reported that methane production was significantly decreased when OLR was sharply increased in a UASB reactor working with molasses wastewater. The OLR value was maintained for a period of about 2 weeks, but no improvement was observed in methane production rate and the effluent quality.…”
Section: Resultssupporting
confidence: 92%
“…However, methane production was reduced from 200 to less than 70 L CH 4 kg −1 VS in period c, indicating potential disturbance of the anaerobic process, while the acetate content was more than 35 mmol L −1 . This observation is in line with the results of De Vrieze et al who reported that methane production was significantly decreased when OLR was sharply increased in a UASB reactor working with molasses wastewater. The OLR value was maintained for a period of about 2 weeks, but no improvement was observed in methane production rate and the effluent quality.…”
Section: Resultssupporting
confidence: 92%
“…Both classes, Methanobacteria and Thaumarchaeota have been related with high salinity environments. For instance, De Vrieze et al [67] showed than in anaerobic digestion tanks, Methanobacteriales were selectively enriched as increasing salinity, and Guan et al [68] showed that Thaumarchaeota were the most prevalent Archaea in oceanic deep hypersaline anoxic basins (DHABs). The wide tolerance of these organisms to salinity may allow their presence along the salinity gradient studied.…”
Section: Plos Onementioning
confidence: 99%
“…FO-concentration of A-sludge increased the VFA conversion efficiency from 10 % to 45 % (4.4-fold), which is higher than previously reported [11]. It has been described that high salinity and high conductivity (above 30 mS cm -1 ) negatively affect methanogenesis while acetogenic bacteria can acclimatize to high salt concentration and produce VFA [34]. FO-concentration of A-sludge could be a strategy to increase VFA production (sections 3.4 and 3.5) and, inhibit methanogens due to RSD, thus allowing VFA accumulation in a continuous system.…”
Section: Strategies To Further Increase Vfa Production After A-sludgementioning
confidence: 54%
“…Higher concentrations still might be needed in order to produce VFA from FO-concentrated domestic wastewater, however this would further increase contact time in the FO, le ading to more draw solutes leaking and increased conductivity. Such highly conductive feedstocks could be used for VFA accumulation as conductivity above 30 mS cm -1 negatively affects methanogenesis while acetogenic bacteria still produce VFA at high salt concentrations De Vrieze et al [26]. However, an economic assessment would be required as draw solute leakage comes at a cost.…”
Section: Fermentation Yields Of the Different Streamsmentioning
confidence: 99%